Difficulties in the privatisation and reorganisation of the agricultural enterprises in Russia - David B. Epstein; Jürgen Siemer (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 1998)
Presently Russia is experiencing the complicated process of transforming the economic system of central planning into a socially oriented market economy. Of great importance for the success of this process is the institutional reshaping of the agricultural sector, particularly the privatisation of land and assets. In this paper the procedure and the problems of privatising Russian agriculture are extensively discussed against the background of the unfavourable development of the Russian agricultural sector. – – Gegenwärtig durchläuft Rußland einen komplizierten Prozeß der Transformation des zentral geplanten Wirtschaftssystems in eine soziale Marktwirtschaft. Von großer Bedeutung für den Erfolg dieses Prozesses ist der institutionelle Wandel des landwirtschaftlichen Sektors, insbesondere die Privatisierung von Land und sonstigem Vermögen. Vor dem Hintergrund der ungünstigen Entwicklung der russischen Landwirtschaft werden in dieser Arbeit die Vorgehensweise und die Probleme der russischen Landwirtschaft ausführlich diskutiert.
urn:nbn:de:gbv:3:2-22679
Keywords: 330; Landwirtschaft; Übergangswirtschaft; Agrarreform; Privatisierung; Reorganisation; Russland